2007
DOI: 10.3998/ark.5550190.0009.304
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a new tricylic ring system: [1,2,3]triazolo[1,5-b]cinnolinium salt

Abstract: Synthesis of the first representative of the linearly fused [1,2,3]triazolo [1,5-b]cinnolinium heteroaromatic cation as a quaternary salt is reported. Improved reaction conditions for preparation of some precursors have been elaborated. Reaction of the new heteroaromatic salt with nucleophiles resulted in regioselective formation of zwitterionic products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Our literature survey indicated that similar ring closure with quinoxalines have been described: Boguslavskiy et al 21 described that treatment of 2-quinoxalylketone hydrazones with diluted sulfuric acid on air resulted in fused pyrazoles, whereas Sarodnick et al carried out similar ring closure in xylene at high temperature in the presence of chloranil. 22 In one of our recent publications, 23 we have reported on difficulties with transformation of 3-cinnolylketones (10) to hydrazones, and only the 4-nitrophenyl derivative (11) could be isolated. We have now found that with treatment of the majority of these ketones with arylhydrazines, a spontaneous ring closure to pyazolo[4,3-c]cinnolines (12) occurs (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our literature survey indicated that similar ring closure with quinoxalines have been described: Boguslavskiy et al 21 described that treatment of 2-quinoxalylketone hydrazones with diluted sulfuric acid on air resulted in fused pyrazoles, whereas Sarodnick et al carried out similar ring closure in xylene at high temperature in the presence of chloranil. 22 In one of our recent publications, 23 we have reported on difficulties with transformation of 3-cinnolylketones (10) to hydrazones, and only the 4-nitrophenyl derivative (11) could be isolated. We have now found that with treatment of the majority of these ketones with arylhydrazines, a spontaneous ring closure to pyazolo[4,3-c]cinnolines (12) occurs (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…In one of our recent publications, we have reported on difficulties with transformation of 3-cinnolylketones ( 10 ) to hydrazones, and only the 4-nitrophenyl derivative ( 11 ) could be isolated. We have now found that with treatment of the majority of these ketones with arylhydrazines, a spontaneous ring closure to pyazolo[4,3- c ]cinnolines ( 12 ) occurs (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Primary Applications : Use as highly conjugated linkers in triazole-based polymers [ 4 ] for the evaluation of solar cell materials is the main reported application. 1,2,3-Triazolo[1,5-b]pyridazines : The most common synthetic method is treatment of a keto-substituted pyridazine with p -bromophenyl hydrazine hydrochloride forming the hydrazone, then treatment with TBP in DCM [ 87 , 88 ]. A report of intramolecular cyclization of a diketo-oxime has been reported [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2,3-Triazolo[1,5-b]pyridazines : The most common synthetic method is treatment of a keto-substituted pyridazine with p -bromophenyl hydrazine hydrochloride forming the hydrazone, then treatment with TBP in DCM [ 87 , 88 ]. A report of intramolecular cyclization of a diketo-oxime has been reported [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation